Correlation between mean arterial pressure (MAP) and length of stay (LoS) of heart failure in-patients with sacubitril/valsartan and ramipril at X Hospital Semarang - Hadianti Deliana R; N Setiawati, Maria Caecilia; Fef Rukminingsih (Indonesian Journal of Pharmacology and Therapy, 2026)
Heart failure is a health problem with high morbidity and mortality rates globally and nationally, so optimal therapy is needed to improve clinical outcomes and efficiency. Sacubitril/valsartan (angiotensin receptor neprilysin inhibitor/ARNI) and ramipril (ACE inhibitor/ACEi) have become the therapeutic options in heartfailure patients. However, the effectiveness of both therapies on length of stay (LoS) and changes in mean arterial pressure (MAP) in the Indonesian population has not much studied. This study used an observational retrospective design on the medical record data of heart failure inpatients at X Hospital, Semarang,during January to December 2024 period. All in-patients who received sacubitril/valsartan or ramipril therapy (in combination with beta blockers and aldosterone receptor antagonists) were included, and were differentiated based on changes in MAP (up, down and constant). Correlation statistical analysis was performedwith normality test, Kruskal-Wallis, and Anova tests to correlate the LoS and MAP changes between therapy. A total of 131 patients were categorized by therapy and MAP changes. The average LoS on Sacubitril/valsartan and Ramipril therapy was approximately 5–6 d each for the entire MAP change group. Statistical testsshowed no significant difference between the two therapies for LOS, as well as of MAP changes (p > 0.05). MAP changes (up, down, constant) in heart failure in-patients treated with sacubitril/valsartan and ramipril provided variation in LoS, but the differences were not statistically significant between the two therapies.